Metaphors and Novel Allusions, Two Prominent Stylistic Features in Bidel’s Sonnets - Rajab Tohidian; Mohammad Akbari Habashi (مطالعات زبانی و بلاغی)
Consciuos avoidance of stereotypically prevalent structures both in meaning and imagination is one of the salient features of Bidel Dehlavis poetry which extensively enhances his works’ innovation, effectiveness and delightfulness. This ambigious parameter significantly appear in metaphors and allusions. Bidel Dehlavi’s sonnet scope from artistical efficiency could be divided into two forms: Simple and Difficult. The former refers to comprehensively simple metaphors which do no create so much ambiguity, but the latter group comprise widely frequent metaphors which play prominent role in his expression. The second area of ambiguity in Bidel’s works relies in using allusions. It could be claimed that the part of allusions which seem oblique and unaccustomed orginates in customs, traditions, folklore, Iranian and Indian spoken language and Bidel’s symbolic expression. Accordingly, the sole route to get aquintance with his traditions, lookview, lifestyle and verbal features is deconstruction. Thereupon, the present study initially attempts to specify meaning innovation scope and then giving inexpicable and unfamiliar examples determine his artistic adroit and skill.